2020
DOI: 10.3389/fcimb.2020.00495
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Gut Microbes and L-Thyroxine Through Altered Thyroxine Metabolism in Subclinical Hypothyroidism Subjects

Abstract: Yao et al. Gut Microbes Influence L-Thyroxine Treatment composition. The reason may due to the differences in thyroxine metabolic capacity in gut. In addition, the metabolic similarity of iodothyronines and bile acid in gut also provides possibilities for the correlation between host's thyroxine and cholesterol levels. This study was registered with ClinicalTrials.gov as number NCT01848171.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 54 publications
2
21
1
3
Order By: Relevance
“…In the current study, the use of thyroid hormones (thyroxine) resulted in a significant increase in the alpha diversity of the oral cavity, whereas previous reports of gut microbial diversity in patients taking the thyroid hormone thyroxine showed no statistical differences from controls (not receiving thyroxine) [ 44 ]. Khan and associates investigated the impact of statins on gut microbiome composition and reported differences in alpha and beta diversity measures, with more variability in the untreated hypercholesterolemic patients (n = 15) compared to statin-treated hypercholesterolemic patients (n = 27) or non-hypercholesterolemic individuals (n = 19) [ 45 ].…”
Section: Discussioncontrasting
confidence: 65%
“…In the current study, the use of thyroid hormones (thyroxine) resulted in a significant increase in the alpha diversity of the oral cavity, whereas previous reports of gut microbial diversity in patients taking the thyroid hormone thyroxine showed no statistical differences from controls (not receiving thyroxine) [ 44 ]. Khan and associates investigated the impact of statins on gut microbiome composition and reported differences in alpha and beta diversity measures, with more variability in the untreated hypercholesterolemic patients (n = 15) compared to statin-treated hypercholesterolemic patients (n = 27) or non-hypercholesterolemic individuals (n = 19) [ 45 ].…”
Section: Discussioncontrasting
confidence: 65%
“…Considering the patient group receiving oral thyroid hormone replacement therapy as a whole (irrespective of the dose) versus those with no treatment, the abundance level of bacteria belonging to the genus Ruminococcus, which is prevalent in human gut microbiota, was elevated in the group with no treatment. Similar findings were made with regard to the bacteria representing the genera Alistipes and Anaerotruncus [54]. Researchers from the University of Bradford studied the possible effects of thyroxine on the performance of spatial learning tasks, where cholinergic activity and hippocampal function are of key importance.…”
Section: The Impact Of Oral Thyroid Hormone Supplementation On Microbiomesupporting
confidence: 55%
“…Lauritano et al studied 50 patients with HT and 40 controls and found that 54% of patients presented SIBO, in contrast with the control group ( 4 ). A clinical trial conducted by Yao et al ( 42 ) demonstrated that the intestinal microbiota in patients with hypothyroidism, randomly divided to receive L-thyroxine ( N = 49) or no treatment ( N = 68), did not show significant differences with respect to alpha diversity. However, the relative abundance of Enterococcus and Odoribacter genera varied slightly depending on the dosage of L-thyroxine ( 42 ).…”
Section: Discussionmentioning
confidence: 99%